Karakteristik Termal Briket Kayu Sengon Dengan Variasi Suhu Tekan - Nasrul Ilminnafik; M. Agung Fauzi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2015)
Briquette is a solid fuel that made from organic waste and mixed with other materials by pressure. In this research, the raw material used is waste of sengon sawdust and used tapioca flour as binder. This study focused on the effect of temperature pressure variations on ignition time, burning time and the rate of combustions of briquette charcoal sengon. Pyrolisis temperature 400 ºC and variation of temperature pressure were 150ºC, 175ºC, and 200ºC. The results of research onsuppression temperature of 200 ºC, the ignition time is getting longer, because the more water out of charcoal and tapioca, it makes active adhesive particles to bind the charcoal leading to higher density briquettes. On suppression temperature of 200 ºC, the burning time is getting longer, because more and more moisture out of charcoal and tapioca, so that more particles tapioca that binds the active charcoal. On pressure of 200 ºC, the slower the rate of combustion because the evaporation of the water content of charcoal and tapioca so that the higher the water content out of the adhesive will more actively bind charcoal and increase density of briquettes. Keywords: briquettes sengon, thermal characteristics, ignition time, burning time, rate of combustion.